TO DEVELOP SKILLS OF SPEAKING IN B1 LEVEL STUDENTS - Sh.Xoldorova (Journal of Higher Education and Academic Advancement, 2024)
This article aims to explore effective methods for developing speaking skills in B1 level students, focusing on the importance of communicative competence. Through a literature analysis, various strategies will be examined to identify key elements that contribute to successful language acquisition at this level. The methods section will outline practical approaches for educators, incorporating interactive activities and motivation techniques. The results section will present the outcomes of applying these methods, followed by a discussion that delves into the implications of the findings. Finally, the article will conclude with suggestions for further research and practical recommendations for teachers.